Faktor Faktor Keteraturan Minum Obat pada Penderita Tuberkulosis di Indonesia (Analisis Data SKI 2023) - Trynanda Samosir; Helmi Suryani Nasution; Rd Halim (Jurnal Kesehatan Amanah, 2026)
Tuberculosis (TB) remains one of the leading infectious causes of death worldwide and continues to pose a major public health challenge. The disease is caused by Mycobacterium tuberculosis and is transmitted through airborne droplets when infected individuals cough or speak. Without treatment, TB has a mortality rate of approximately 50%; however, about 85% of patients can be successfully treated with anti-tuberculosis drugs administered for 4–6 months according to standard guidelines. Indonesia is among the eight countries contributing the highest number of TB cases globally, yet national treatment adherence remains suboptimal. This study aimed to analyze factors associated with medication regularity among pulmonary TB patients in Indonesia using data from the 2023 Indonesian Health Survey. A cross-sectional design was applied using secondary data from respondents aged ≥15 years who had been diagnosed with TB and received treatment, with a weighted sample of 667,421 individuals. Data were analyzed using univariate, bivariate (Rao-Scott Chi-Square), and multivariate logistic regression with backward elimination. The prevalence of regular medication intake was 72.21%. Education level, residence, presence of a treatment supervisor (PMO), type of therapy, and comorbidities were significantly associated with medication regularity. Multivariate analysis identified the presence of a PMO as the most dominant factor, followed by higher education and absence of comorbidities. Strengthening treatment supervision and implementing Health Belief Model–based health education are essential to support the 2030 TB elimination target in Indonesia.